THE EFFECT OF LEARNING METHODS ASSISTED BY SAS (SYNTHETIC ANALYTICAL STRUCTURES) WITH LETTER CARD MEDIA ON PARTICIPANTS' BEGINNING READING ABILITY STUDENTS AT PRIMARY SCHOOL 49 BANDA ACEH - Helminsyah Helminsyah; Mardhatillah Mardhatillah; Dafita Oyani (Teunuleh Publisher, 2020)
The research objective was to determine the effect of the SAS (Synthetic Analytical Structure) learning method assisted by letter card media on students' initial reading skills at Primary School 49 Banda Aceh on the theme of clean and healthy life in school. This research was conducted by pre-experimental method with one group pretest-posttest design which was held at Primary School 49 Banda Aceh, in the odd semester of the 2018/2019 academic year. The sample in this study were students of grade II Primary School 49 Banda Aceh with a total of 28 students. Data collection was carried out by giving students pre-test reading questions in the form of command questions as many as 10 pre-test questions and 10 post-test questions. A normality test is done to see the normality of the data and showed that the data were normally distributed with an average value calculated < table (3.8597 <11.07). Based on the results of the study, it can be concluded that there is an effect of the use of the SAS learning method assisted by card media on the improvement of students' initial reading skills at Primary School 49 Banda Aceh with a value of tcount > ttable (10.147> 1.703), while in the test the increase in N-Gain is a high category. Percentage 57.14%, and 42.86% medium category. The conclusion is that there is an increase in the beginning reading ability of students who are taught using the SAS method aided by letter card media.